Neuroprotective effect of Quince leaf hydroalcoholic extract on intracerebroventricular streptozotocin-induced oxidative stress in cortical tissue of rat brain - A Hajizadeh Moghaddam; M Mohajerani; E mohammadi (Armaghane Danesh Bimonthly Journal, 2015)
Background & aim: Oxidative stress is a result of the imbalance between free radicals and the antioxidant system of the body. Increased oxidative stress in brain causes dysfunction of brain activities, destruction of neurons, and disease such as Alzheimer. Antioxidants, for example vitamins, phenolic compounds and flavonoids have been extensively investigated as potential therapeutic agents in vitro and in vivo for prevention of neurodegenerative diseases. In the present experimental study, the neuro-protective effect of quince leaf hydroalcoholic extract (QLHE) on intracerebroventricular streptozotocin (icv-STZ)-induced oxidative stress in cortical tissue of rat brain was examined.